Review of Maqashid Sharia and MUI DSN Fatwa on Takaful Products of Education Funds at PT Asuransi Takaful Keluarga Yogyakarta - Hakim , Umm Habibah; Alfat, Abdul Fatahillah (DIKTUM: Jurnal Syariah dan Hukum, 2023)
Sharia tendencies in the modern era This pushes the progress and development system toward a more inclusive sharia economy. Contracts that are emblematic of Islamic economics may be negotiated. One of them is incorporated into the product takaful (sharia insurance). Study This compares theory maqashid sharia and DSN MUI fatwas in insurance product contemplation education. Study This includes a qualitative research in which theory maqashid sharia and DSN fatwa serve as an analytical knife. There are three aggregated contracts _ in practice Education Fund Takaful insurance, including contracts mudharabah, wakalah bill ujrah, and tabarru', according to research results. In maqashid sharia, practice Education Fund Takaful insurance provided protection in three (3) aspects. Protection to benefit reason (hifdz al- Aql) in the form of protection for child related to his education when the parents captured calamity, wealth (hifdz al-Maal) in the form of invest ten participant with wealth (hifdz al-Maal) Be cautious in accordance with sharia principles carried out by parties' company and (hifdz an- Nasl) in the form of compensation for expert legacy that has been left behind.